PENGARUH EVENT MARKETING DAN BRAND EXPERIENCE TERHADAP LOYALITAS KONSUMEN PADA KOPI NAWNAW DI TASIKMALAYA - Riki Aksan Aji Ashari Riki; Depy Muhamad Pauzy; Dudu Risana (Veteran Economics, Management, & Accounting Review, 2026)
The increasingly intense competition in the coffee shop industry requires business owners to develop marketing strategies that can enhance customer loyalty. One of the strategies that can be implemented is the application of event marketing and the creation of a positive brand experience. This study aims to analyze the simultaneous and partial effects of event marketing and brand experience on customer loyalty at Kopi NawNaw Tasikmalaya. This research employed a quantitative method with a causal approach. The sampling technique used was purposive sampling, involving 100 respondents. Data were collected through questionnaires, while data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The results indicate that event marketing and brand experience simultaneously have a significant effect on customer loyalty. Partially, event marketing has a positive and significant effect on customer loyalty. Likewise, brand experience also has a positive and significant effect on customer loyalty.